Health Care Systems Redesign Project to Improve Dysphagia Screening. Issue 3 (July 2015) - Daggett, Virginia S.; Woodward-Hagg, Heather; Damush, Teresa M.; Plue, Laurie; Russell, Scott; Allen, George; Williams, Linda S.; Chumbler, Neale R.; Bravata, Dawn M.
<x xml:space="preserve">Abstract</x> The purpose of this project was to improve dysphagia-screening processes in a tertiary Veterans Affairs Medical Center. The dysphagia-screening tool was redesigned on the basis of frontline clinician feedback, clinical guidelines, user satisfaction, and multidisciplinary expertise. The revised tool triggered a speech-language consult for positive screens and demonstrated higher scores in user satisfaction and task efficiency. Systems redesign processes were effective for redesigning the tool and implementing practice changes with clinicians involved in dysphagia screening.